Comparative Analysis of the Role of Social Environment (Bandura) and Cultural Mediation (VYGOTSKY) in Character Education Literature - Musfirah Nadjamuddin; Dika Tripitasari; Muhdin Muhdin (International Journal on Advanced Science, Education, and Religion, 2026)
This Study aims to conduct a theoretical deconstruction of the mechanisms of student discipline formation by comparing two major perspectives: Albert Bandura's Social Learning Theory and Lev Vygotsky's Socio-Cultural Theory. The research method used is library research with a qualitative descriptive approach. Data analysis was conducted through content analysis techniques on primary and secondary works relevant to both figures. The results of the study indicate that, according to Bandura, discipline is constructed through modeling and vicarious reinforcement mechanisms that culminate in the formation of self-efficacy. Meanwhile, Vygotsky emphasized that discipline is a product of the internalization of cultural values ​​mediated by language and scaffolding within the Zone of Proximal Development (ZPD). The conclusion of this study confirms that ideal student discipline is the result of a synergistic combination of imitation of appropriate role models and conscious internalization of cultural values. The implications of this study offer a framework for educational institutions to integrate aspects of the visual environment (role models) and dialogic interaction (interpretation of rules) in character education curricula